UJI KARAKTERISTIK CAMPURAN MINYAK KELAPA SAWIT DENGAN MINYAK BIJI BUNGA MATAHARI SEBAGAI ISOLASI PADA TRANSFORMATOR - Putra, Deni Dwi Rahman; Dhofir, Moch.; Utomo, Teguh (Jurnal Mahasiswa TEUB, 2024)
Transformer oil is a type of liquid insulation used for insulators and coolants in transformers. Until now, the main component in insulating oil production still predominantly comes from petroleum. The availability of petroleum will increasingly run out because petroleum is a non-renewable material. Efforts are needed to reduce the use of petroleum, one way that can be done is to use vegetable oil as liquid insulation. One of the vegetable oils that can be used as liquid isolation is palm oil. However, palm oil still has a low dielectric strength, so sunflower seed oil which has a high dielectric strength is mixed so that the dielectric strength of palm oil can be increased. This research discusses the effect of adding sunflower seed oil to palm oil on the electrical properties of relative permittivity and conductivity as well as breakdown voltage. So in this research four tests will be carried out, namely water content reduction testing, relative permittivity testing, conductivity testing and breakdown voltage testing. The sunflower seed oil used uses a composition of 5%, 10%, 15%, 20%, 25%, 30%. Based on the test results that have been carried out, palm oil has a breakdown voltage value of 24.85 KV/2.5 mm. This causes the breakdown voltage value to not meet the IEC 156 standard of 30 KV/2.5 mm. Mixing sunflower seed oil with palm oil can increase the breakdown voltage value of palm oil. The more sunflower seed oil in the composition, the breakdown voltage value will also be greater. A composition of 30% sunflower seed oil has abreakdown voltage value of 44.89 KV/2.5 mm. The value of reducing water content, relative permittivity and conductivity of palm oil is quite large with values respectively 600 PPM; 3.56 F/m; 19.9 × 10^(-10) S/m. The greater the composition of the sunflower seed oil mixture, the reduction in water content, relative permittivity and conductivity will decrease. A mixture with a composition of 30% sunflower seed oil has relative permittivity and conductivity values of 300 PPM respectively; 3.2; 2.12 × 10^(-10) S/m. This shows that the greater the composition of sunflower seed oil, the better the insulating quality. When compared with Shell Diala-B mineral oil, it has a breakdown voltage of 19.61 KV/2.5 mm with a relative permittivity value of 2.95 and a conductivity value of 1.99 × 10^(-10) S/m and a water content reduction value of 0 PPM. Keywords— mixture, palm oil, sunflower seed oil, breakdown voltage, conductivity, relative permittivity